EFEKTIVITAS FUNDRAISING PROGRAM PESANTREN MULIA (MASA LANJUT USIA) - Resky Yunazan Putra (Peksos: Jurnal Ilmiah Pekerjaan Sosial, 2023)
Mulia Islamic boarding school is a program organized by the Sinergi Foundation Institute. The Mulia Islamic Boarding School program is a fundraising program which aims to raise funds and collect donors from the participants of the Mulia Islamic Boarding School program. The aim of this research is to describe the effectiveness of fundraising for the Pesantren Mulia (Senior Age) program, to describe the obstacles and efforts in fundraising for the Pesantren Mulia (Senior Age) program, and to describe the practical implications and theoretical implications of fundraising for the Pesantren Mulia (Senior Age). The method used in this research is a qualitative method descriptive approach. The data collection techniques used were interviews, observation, document study, coding and SWOT analysis. The informants in this research consisted of six informants. Two fundraising divisions of the Mulia Islamic Boarding School program as main informants, two alumni of the Mulia Islamic Boarding School program participants as supporting informants, and two potential informants of the Mulia Islamic Boarding School program participants as supporting informants. The results of this research are that the Islamic Boarding School Mulia fundraising program is said to be effective because it can meet the measures of effectiveness of a program. Measures of effectiveness are program success, target success, satisfaction with the program, level of input and output, and overall goal achievement.